2007
DOI: 10.1016/j.vph.2007.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of PKC or protease inhibitors on acute pancreatitis-induced tissue injury in rats

Abstract: Background: Acute pancreatitis (AP) is still one of the severe diseases that cause the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Other studies using AEBSF to block serine proteases at concentrations over 1 mM did observe cell death or toxicity in primary bone and osteoblastic cell (Gorski et al 2009) as well as in RAW264.7 cell cultures (Wijayanti et al 2005). Furthermore, studies with in vivo inhibition of serine proteases with AEBSF in mice have reported no overt toxicity (Buitrago-Rey et al 2002;Shi et al 2007;Megyeri et al 1999). However, an increase in cell death may occur in AEBSF-exposed cells with longer culture periods, or at a higher dose, or in cells at different developmental/activation stages.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies using AEBSF to block serine proteases at concentrations over 1 mM did observe cell death or toxicity in primary bone and osteoblastic cell (Gorski et al 2009) as well as in RAW264.7 cell cultures (Wijayanti et al 2005). Furthermore, studies with in vivo inhibition of serine proteases with AEBSF in mice have reported no overt toxicity (Buitrago-Rey et al 2002;Shi et al 2007;Megyeri et al 1999). However, an increase in cell death may occur in AEBSF-exposed cells with longer culture periods, or at a higher dose, or in cells at different developmental/activation stages.…”
Section: Discussionmentioning
confidence: 98%
“…Inhibition of the neutrophil infiltration can attenuate the pancreatic injury. 23 Treatment with alpha-pinene significantly decreased the pancreatic MPO levels probably due to its anti-inflammatory action. One of the lipid peroxidation marker, which is elevated in L-arginine treated rats.…”
Section: Assessment Of Interleukins and C-reactive Proteinmentioning
confidence: 94%
“…Much of the data in the literature on the mechanisms of PKC isoform involvement in ARDS pathogenesis is inferred indirectly from studies in which pharmacological modulation of PKC activity (6264), or the use of knockout mice for specific PKC isoforms (65, 66), is correlated with improvements in commonly employed experimental animal models of lung injury.…”
Section: Pkcs and Pathogenesis Of Ardsmentioning
confidence: 99%
“…The PKC inhibitor polymixin B (broad spectrum inhibitor which also binds endotoxin) attenuated lung injury and lowered levels of TNF-α, IL-1β, MCP-1 and IL-10 in a murine model of lung injury secondary to acute pancreatitis, suggesting that broad spectrum PKC inhibition dampened the overall inflammatory response in the lung (64). Similarly, systemic infusion of staurosporine (broad spectrum inhibitor which also inhibits PKA and PKG) and polymixin B both reduced pancreatic and pulmonary MPO levels in a rat model of acute pancreatitis (62). …”
Section: Pkcs and Pathogenesis Of Ardsmentioning
confidence: 99%